Mapping the Flood Vulnerability Levels in the Ciliwung River Basin, Bogor City: PEMETAAN TINGKAT KERAWANAN BANJIR PADA DAERAH ALIRAN SUNGAI CILIWUNG KOTA BOGOR - sri, Sri Rejeki O.laoli; Wiwik Yuniarni; Rindang Alfiah (MATRAPOLIS: Jurnal Perencanaan Wilayah dan Kota, 2025)
Between 2013 and 2023, floods were Indonesia's most frequent and impactful disasters. In Bogor City, the high intensity of flooding has led to significant economic losses, infrastructure damage, and casualties. Aside from heavy rainfall, one of the main contributing factors is land use change. The area that has undergone the most significant land use transformation is the Ciliwung River Watershed in Bogor City, which has resulted in the watershed functioning suboptimally. Over the past seven years, 160 recorded flood events in Bogor City have been recorded, indicating that this issue has become increasingly complex and requires a strategic and practical management approach. One effort to mitigate the impact of flooding is mapping flood vulnerability within the Ciliwung Watershed. Between 2013 and 2023, floods were the most frequent and impactful disasters in Indonesia. In Bogor City, the high intensity of flooding has resulted in significant economic losses, damage to infrastructure, and casualties. In addition to heavy rainfall, changes in land use have been a major contributing factor. The Ciliwung River Watershed in Bogor City has experienced the most significant land use transformation, which has led to the watershed functioning suboptimally. Over the past seven years, 160 flood events have been recorded in Bogor City, indicating that this issue has grown increasingly complex and requires a strategic and practical management approach. To mitigate the impact of flooding, one initiative has been to map flood vulnerability within the Ciliwung Watershed. This process aims to assess vulnerability levels across the area and identify strategies to reduce the risk of flood disasters. Therefore, this study aims to determine the level of flood vulnerability using scoring and overlay methods and identify priority flood management strategies suitable for implementation in Bogor City. Based on the analysis, vulnerability levels in Bogor City are categorized into four classes. The most appropriate strategy for managing floods in the Ciliwung Watershed is to optimize existing strengths and opportunities to enhance flood resilience.